Studi Literatur Peran Kepemimpinan Dalam Perubahan dan Perkembangan Organisasi - Muhammad Anshari Hutasuhut; Nuri Aslami (Universitas Muhammadiyah Enrekang, 2022)
One of the factors influencing an organization's performance is its leadership, particularly when it comes to implementing change. It is preferable to first understand what the term leader means in order to comprehend what is meant by leadership (leadership) (leader). This is so that a leader, who performs the task of performing the leadership action, can exercise leadership. This study combines qualitative research methodologies with strategies for analyzing literature reviews. The following describes transformative leadership. (1) According to Bass, charisma, charismatic influence, or idealized influence, is an emotional aspect of leadership that typically refers to the strength of the leader who is able to have a significant influence on his followers. (2) Leadership that inspires and encourages people to accomplish goals is known as inspiring motivating. (3) By encouraging